Exploring intermediary practices of collaboration in university? industry innovation: A practice theory approach - Murphy, Stephen (My University, 2022)
The intensity of the global and distributed economy requires innovative efforts that single organizations often cannot develop alone. Collaborative innovation is traditionally studied in terms of collaborative process to maintain and outcomes to implement. However, collaborations relating to innovation often take place in difficult-to-explore spaces in-between. This study adopts a practice-based approach to explore practices of collaboration developed by the university as an intermediary in innovative projects. Drawing on a case study, we identify four micro-practices that appear crucial to initiating and sustaining collaboration: networking, partnering, culture making and supporting. We outline the purpose and constituent objects, doings and knowledge of each practice. This article contributes to ongoing debate around improving the effectiveness of collaborative innovation and provides insights into how a set of apparently insignificant, routinized micro-practices contribute to intermediaries' success in initiating and sustaining collaborations.
PUBLISHED
Keywords: University–industry collaboration; Practice theory; Micro-practices; Innovation intermediary; Collaboration; Creative Technologies; Innovation; Education; Employment